Persepsi Generasi-Z Muslim terhadap Penggunaan QRIS sebagai Digital Payment Berdasarkan Prinsip Syariah - Khikmah, Nurul; Syafi’i, M. Aris; Hermawan Adinugraha, Hendri (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2025)
This study aims to explore Generation-Z Muslims in Pekalongan's perception of QRIS as a digital payment method based on sharia principles and identify their interest & factors that influence their interest in using QRIS. A qualitative approach was used in this research through interviews, documentation, and observation of 30 interviewees. The results found that high interest in QRIS is driven by convenience, efficiency, security and reducing dependence on cash. Generation Z Muslims consider QRIS to be in accordance with sharia principles because it avoids elements of usury, gharar, and maisir, and is transparent in transactions. However, they also face challenges such as unstable internet access and the risk of digital fraud. To support the use of QRIS, the government is expected to improve network infrastructure and digital security education. The results of this study are expected to contribute to the development of digital Islamic financial services in Indonesia.